ESP course evaluation and amelioration on the basis of Needs Analysis: The case of Master 1 at the Institute of Nutrition, Food and Agri-food technologies, University of Constantine 1, Algeria - ELMECHTA , Lamia (Journal of Human Sciences, 2023)
This work purports to analyze the needs of Master 1 students at the institute of Nutrition, Food and Agro-food technologies (INATAA). It aims to evaluate and ameliorate the current ESP course on the basis of needs analysis results. A questionnaire was administered to a sample of 48 Master1 students at the Institute of INATAA. The questionnaire aimed to investigate the students’ needs for the studied ESP course, measure their attitudes, and assess their proficiency level. The findings reveal that the proficiency of the majority of Master 1 students ranges from average to good in receptive skills; yet it proves weak in productive skills. Similarly, most of the subjects show a positive attitude towards the course; however, they still have many weaknesses, notably in productive skills, which are considered problems when engaged in scientific research. These findings have brought a number of insightful recommendations for the amelioration of the course.